The effect of divalent metal cations on endotoxin and plasmid DNA interaction - Elvina Clarie Dullah (2018)
Endotoxin has the ability to undergo a stable interaction with other biomolecules, especially during the production process. Therefore, the removal of endotoxins from the final product is crucial as endotoxin contamination could pose negative effects on human health, including tissue inflammation and damage, fever, sepsis and eventually death. Moreover, endotoxin-biomolecules interaction is considered to be temperature and pH stable, and thus complicating its removability. Some divalent metal cations, including magnesium chloride (Mg2+), calcium chloride (Ca2+) and zinc sulphate (Zn2+), were believed to have the ability to induce endotoxin aggregation, therefore, these cations might potentially interrupt the stable endotoxin-biomolecule binding thus facilitating endotoxin removal. This project focused on the study of the effects of divalent metal cations on endotoxin, as well as its effect in the presence of plasmid DNA (pDNA). The study was conducted under various physicochemical conditions such as types of divalent metal cation, concentration, pH and incubation time. The experiments were divided into three parts; (1) zeta potential analysis of endotoxin, (2) cation bound analysis by using Arsenazo III, and (3) binding tendency of cations on endotoxin with the presence of pDNA. Transmission electron microscopy (TEM) was done for the cation that exerted the most significant effect towards endotoxin. The analysis of zeta potential at different divalent metal cation concentrations and pH values showed that among the three divalent cations studied (Mg2+, Ca2+, Zn2+), Mg2+ had the most significant effect on endotoxin surface charge. The zeta potential of endotoxin reduced from - 43.53 mV to 0.02 mV in the presence of Mg2+, while a value of 0.59 mV was observed at lower pH condition. In the cation-endotoxin binding study using Arsenazo III, Zn2+ showed the highest theoretical number of bound cation (approximately 0.6) compared to Ca2+ and Mg2 + (approximately 0.12 and 0.05 respectively). These values were determined based on the Scatchard plot. Part three of this study showed that the tendency of Zn2+ to bind with endotoxin was higher even in the presence of pDNA. The result was evident from the low intensity of bands on the agarose gels for both pDNA-Zn2+ and endotoxin-pDNA-Zn2+. Ca2+ and Mg2+ did not show any significant changes in band intensity except for the incubation of pDNA and endotoxin-pDNA complex in pH 1. Apparently, Ca2+ and Mg2+ neutralized the negative charge of pDNA and the complex as indicated by the low band intensity. Visualization under TEM further verified that even in the presence of pDNA, the aggregated structure of Zn2+-endotoxin remained unchanged. These findings imply that Zn2+ is more selective towards endotoxin than pDNA. In summary, among the three types of divalent metal cations studied, Zn2+ was found to exert the most significant binding interaction with endotoxin. Cation concentration played a major role in binding with endotoxin, whereas incubation time had little to no effect towards the interaction. These findings could be applied in the downstream processing of pDNA whereby Zn2+ has been found to interrupt the stable binding between endotoxin and pDNA, hence allowing the removal of endotoxin and recovery of pDNA.